A Summary of “Die Wiedergutmachung nationalsozialistischen Unrechts durch die Bundesrepublik Deutschland Band VI – Entschädigungsverfahren und Sondergesetzliche Entschädigungsregelungen” - Kost, Lina; Justus Liebig University Giessen (My University, 2024)
The following article provides a brief summary of the sixth volume of the series “Die Wiedergutmachung nationalsozialistischen Unrechts durch die Bundesrepublik Deutschland” published, among others, by the Federal Ministry of Finance in six volumes, and is accordingly focused on the implementation of the respective compensation laws.
Keywords: ddc:340